HBCUs Online: Can Students With Disabilities Access Historically Black College and University Websites?. (July 2019) - Taylor, Z. W.
On January 18, 2018, U.S. Congress amended Section 508 of the Americans with Disabilities Act (ADA) to hold all Title IV U.S. institutions of higher education to Level AA compliance with web accessibility standards, also known as WCAG 2.0 standards. As a result, this study examined all 100 historically Black college and university (HBCU) websites and found 94 HBCU websites were in violation of ADA and were not web accessible for students with disabilities after the January 18th amendment of Section 508. Using two robust web accessibility software packages, each website was evaluated at both the Level A and Level AA threshold of ADA compliance. The average HBCU website included 62 WCAG errors, meaning the website was likely non-ADA compliant. Furthermore, a majority of errors were minor, as many pictures were missing alt text or a hyperlink was not defined. Implications for practice, research, and HBCU leadership will be addressed.